LITERATURE REVIEW : PENGARUH PROGRAM SELF LEADERSHIP TERHADAP KINERJA PERAWAT DI RUMAH SAKIT - Catharina Dwiana Wijayanti; manik, yeanmariana_24 (Jurnal Keperawatan Widya Gantari Indonesia, 2023)
The quality of nursing services is influenced by the performance of nurses. Nurses who have high self-leadership will have confidence in their own abilities. Self-leadership allows nurses to be able to organize themselves, focus on the goals to be achieved, and have an unyielding nature in solving problems so that it will have an impact on the resulting performance. The aim of the literature review is to analyze the relationship between self-leadership and nurse performance. The search databases used were EBSCO, ProQuest, Elsevier, and Google Scholar. The results of the literature search through a filtering process with PICOT elements obtained 19 studies in the hospital area. The results of the literature analysis show that self-leadership influences many things in a nurse, namely improving the quality of performance, increasing nursing work ethic, and developing a nurse herself. The importance of increasing self-leadership in the form of training for nurses so that they can improve the performance of nursing care for patients. Keywords: Self Leadership, Self Leadership Program, Nurse Performance